KEBIJAKAN FISKAL DALAM PERSPEKTIF EKONOMI SYARIAH - Ranita Pranika; Ahmad Fahrozi; Aziz Hanif Mahfud; Heni Noviarita (STMIK Pringsewu, 2023)
Fiscal policy according to Islamic economics is expected to carry out the functions of allocation, distribution, and stabilization in a country that has certain characteristics of value orientation, and ethical and social dimensions in the income and expenditure of Islamic countries. The focus of the discussion lies on Fiscal policy in Islamic Economics. The purpose of this study is to determine fiscal policy in Islamic economics. The results of the fiscal policy research referred to Islamic teachings precisely according to the social, political, and economic conditions that existed at that time. However, the application of fiscal policy at that time was not necessarily easy to apply today due to constraints, and political, social, and global economic conditions which were quite dominant. So the implementation of fiscal policy, although it cannot be exactly the same as that used in the early days of Islam, needs to adhere to Islamic principles regarding state revenues and expenditures that are oriented towards welfare and a fair distribution of wealth in society.